2007
DOI: 10.1902/jop.2007.060482
|View full text |Cite
|
Sign up to set email alerts
|

Lutheran Blood Group Antigen as a Receptor for α5 Laminins in Gingival Epithelia

Abstract: Lu was in coalignment with Lm alpha5 chain in gingival epithelia. Lu also seemed to have a role in gingival epithelial cell adhesion together with integrin alpha(3)beta(1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Lutheran is a speciWc receptor of 5 chain laminins (Moulson et al 2001;Parsons et al 2001), of which only laminin-511 was found in our cell model. We have shown before that Lutheran is expressed coaligned with laminin 5 chain in normal oral BM (Willberg et al 2007). Here, a strong cell surface-conWned immunoreactivity was evident for Lutheran in 43A cells, whereas in 43B cells, only a diVuse and faint expression was found.…”
Section: Discussionmentioning
confidence: 94%
“…Lutheran is a speciWc receptor of 5 chain laminins (Moulson et al 2001;Parsons et al 2001), of which only laminin-511 was found in our cell model. We have shown before that Lutheran is expressed coaligned with laminin 5 chain in normal oral BM (Willberg et al 2007). Here, a strong cell surface-conWned immunoreactivity was evident for Lutheran in 43A cells, whereas in 43B cells, only a diVuse and faint expression was found.…”
Section: Discussionmentioning
confidence: 94%
“…However, in sickle cell disease (SCD), the vascular endothelium can be substantially damaged, causing exposure of the ECM to the circulation, 8,9 potentially allowing an interaction between erythrocytes and laminin-a5 to occur. 7,10 Such Lu/BCAM-mediated adhesion of sickle erythrocytes to the vascular wall is believed to contribute to vaso-occlusive crises. 11 Activation is required for Lu/BCAM to interact with laminin-a5.…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneously immortalized human gingival keratinocytes (HMK cell line) (Willberg et al, 2007) of passage 24 and human normal gingival fibroblasts (Ruutu, Rautava, Turunen, Tirri, & Syrjanen, 2017) of passage 8 were cultured in standard 96‐well plates in a humidified incubator with 5% CO 2 and 95% air at 37°C until the confluence of 60% per well. Cells were passaged at regular intervals using 25% trypsin.…”
Section: Methodsmentioning
confidence: 99%